Pengaruh Perputaran piutang dan Perputaran Persedian Terhadap Profitabilitas pada Perusahaan Food and beverge yang listing di BEI tahun 2010-2012 - Putra, Riddho Perdana; Hadi, Sudharto Prawata; Prihatini, Apriatni Endang (Jurnal Ilmu Administrasi Bisnis, 2015)
Operational objective of the company is achieving maximum profitability levels. Profitability is the ability of management companies to produce or obtain the profit effectively and efficiently. Fluktuations in profitabilitu experienced food and beverages company, and iconsistencies in the results of previous research encourage researcher to conduct this researchThe ratio that used for the profitability is ROI because it can identify the ability of management companies in managing the assets under their control to generate the income. In the dupont system profitabilitu is affected by asset turn over and profit margin.This study is aimed to identify the influence of receivables turnover and inventory turn over against the profitability of food and beverages company and which variable that had predominant influence of profitability.The population in this research are all food and beverages company of what listed at Indonesia stock exchange in the year 2010-2012. Samples was taken by purposive sampling methode with the result that selected 14 companies as a apotheosis. The type of this study was explanatory research-the variables was counted by utilizing regression analysis methode with SPSS software aids.The study inhibited the account recievable had an influence against company’s profitability, because tcencus (3.392) > ttable (2.028), whereas inventory variable had not influence toward profitablity. it could be sought in coefficient correlation test in which obtained tcencus (-1.174) > ttable (2.028). 0.213 was resulted as determination coefficient (R2), which meant the capability of recievable turnover variable for variation variable ROI explanation was 21.3%, meanwhile the balance 78.7% was adduced by other variables, which was not included within the research. In the future to attention of averages account receivable and increase sales.